2021
DOI: 10.1016/j.tige.2020.10.004
|View full text |Cite
|
Sign up to set email alerts
|

Safety in Endoscopy for Patients and Healthcare Workers During the COVID-19 Pandemic

Abstract: This is a PDF file of an article that has undergone enhancements after acceptance, such as the addition of a cover page and metadata, and formatting for readability, but it is not yet the definitive version of record. This version will undergo additional copyediting, typesetting and review before it is published in its final form, but we are providing this version to give early visibility of the article. Please note that, during the production process, errors may be discovered which could affect the content, a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
19
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(19 citation statements)
references
References 79 publications
0
19
0
Order By: Relevance
“…This technique does not discriminate between live virus and non-infectious viral particles. Only a few studies have reported live SARS-CoV-2 in the stools of COVID-19 patients[ 23 - 26 ]. There is also limited evidence on the duration of fecal viral shedding[ 7 ].…”
Section: Discussionmentioning
confidence: 99%
“…This technique does not discriminate between live virus and non-infectious viral particles. Only a few studies have reported live SARS-CoV-2 in the stools of COVID-19 patients[ 23 - 26 ]. There is also limited evidence on the duration of fecal viral shedding[ 7 ].…”
Section: Discussionmentioning
confidence: 99%
“…Although there are significant concerns about the risk of spread of the virus from an infected patient to endoscopy staff, the overall risk if appropriate precautions are followed appear to be low ( 22 ). In addition to the patient-related processes mentioned earlier, other suggested steps within the endoscopy unit include the use of personal protective equipment, limitations on the number of staff in the endoscopy suite and procedural modifications.…”
Section: Methodsmentioning
confidence: 99%
“…The units prioritized the case using urgent, semi-urgent, and elective classifications [13]. Gastrointestinal endoscopy is performed only on potentially life-threatening conditions (urgent), such as gastrointestinal bleeding, foreign body retrieval, urgent nutritional access, cancer patient, and other conditions that cannot be postponed [9,10].…”
Section: Safety In Gi Endoscopymentioning
confidence: 99%
“…Endoscopic procedures should be performed with safety precautions for patients and also healthcare workers [9]. Rashid emphasized that the endoscopy unit should be reorganized to facilitate procedures as safely as possible along with general measures and COVID-19 screening [10].…”
Section: Introductionmentioning
confidence: 99%